Are there any risks of the disposal of pesticide effluents in soils? Biobed system meets ecotoxicology ensuring safety to soil fauna - Carniel L.S.C.* (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature.The biobed is a purification system, which reduces soil pollution for receiving pesticide residues from handling and washing machinery in agricultural areas. The aims of this study were (1) to assess ecotoxicity effects over time to soil fauna, posed by Lorsban® 480 BR (Chlorpyrifos) and Dithane® NT (Mancozeb) residues when disposed of in a biobed system compared with two subtropical soils, and (2) to assess ecotoxicity effects over time to soil fauna simulating an accidental spillage with Lorsban® 480 BR at the biobed. A semi-field experiment was conducted for 420 days in southern Brazil, testing continuous disposal of washing pulverization tanks in biobeds, Typic Haploperox or Typic Hapludults. In addition, different biobeds received a single dose (1 L) of Lorsban® 480 BR to simulate an accidental spillage. Chronic ecotoxicity tests were performed using Folsomia candida, Eisenia andrei, and Enchytraeus crypticus in different sampling times for both experiments. F. candida was the most sensitive species. The biobed system was able to eliminate effects from residues of both pesticides over time in all species, which did not happen in both natural soils. In accidental spillage simulation, even 420 days after contamination, F. candida did not show reproduction. The biobeds can be a feasible alternative for the disposal and treatment residues of pesticides, also for handling and washing pesticides activities. The system was efficient in promoting degradation and reducing ecotoxicity effects posed by Lorsban® 480 BR and Dithane® NT for soil fauna. It is a safe alternative to avoid soil contamination.